Tinjauan hukum islam terhadap praktik jasa titip (JASTIP) dalam transaksi modern - Zahro, Fatimatuz (Maliki Interdisciplinary Journal, 2025)
The phenomenon of personal shopper services (jastip) has emerged as a modern form of transaction that rapidly developed alongside advances in information technology and society’s increasing demand for domestic and imported products. This study aims to examine the practice of jastip from the perspectives of positive law and Islamic law. Juridically, jastip is considered a valid civil agreement under Article 1320 of the Indonesian Civil Code and is subject to the Consumer Protection Act, the Trade Act, and the Electronic Information and Transactions Act. However, several issues remain, such as price transparency, business legality, and tax compliance. From the Islamic law perspective, jastip is permissible as long as it complies with sharia principles, particularly within the framework of wakalah bil ujrah (agency with compensation), as regulated by DSN-MUI Fatwa No. 113/DSN-MUI/IX/2017. The findings indicate that jastip is legally valid in both positive law and Islamic law, provided that it is conducted with fairness, transparency, and honesty.